The dilemma - Paris, B. A. (St. Martin's Press, 2020)
"A woman's birthday party takes a dark turn in a poignant, heart-stopping new novel from the reigning queen of suspense, NYT and USA Today bestselling author of Behind Closed Doors, The Breakdown, and Bring Me Back"--